(untitled) (CIPEEX, 2025)
This study investigates how the application of the Neoclassical Theory of Administration can optimize efficiency and people management in the Brazilian dairy sector, especially on family farms. Using Data Envelopment Analysis (DEA), it was possible to identify the technical efficiency of the properties and the underutilization of resources. In addition to technical analysis, the study highlights the importance of public policies for modernization and training to address structural challenges, such as lack of technology and infrastructure. The comparison with economies such as South Korea and Taiwan illustrates how strategic investments in management and technology can increase productivity. It is concluded that the balance between structural efficiency and the valorization of human capital is fundamental for sustainable growth in the sector.